PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS STEAM BERORIENTASI ESD UNTUK MENINGKATKAN KREATIVITAS DAN KEMANDIARIAN SISWA - Kusumasari, Seto; Patonah, Siti; Sumarno, Sumarno (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This research aims to develop project-based learning media with a STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach to support strengthening the Pancasila Student Profile, especially in the dimensions of independence and critical reasoning. This research uses a Research and Development (R&D) model with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. The research subjects were students in class 5A of SD Negeri Danasari 01 Tegal Regency, Semester 1 of the 2024/2025 academic year. The development process involved expert validation, practicality testing, and effectiveness evaluation. Learning media is designed using the Canva Platform and Assembler Edu with interactive content including videos, moving images and practice questions. Validation by experts showed very valid results with an average media validity score of 82% and material validity of 86%. The media is considered very practical with a practicality score of 95% by teachers and 80% by students. The implementation of learning media shows significant results in increasing independence (78%) and creativity (76%) in students. Analysis of learning outcomes using the t-test showed that there were significant differences between the experimental class and the control class, with post-test average scores of 79.07 and 66.22 respectively (sig. 0.001 < 0.05). The final evaluation revealed several technical challenges, such as large file sizes and link accessibility, which were addressed through file size optimization and the addition of visual elements. The results of this research show that project-based learning media with a STEAM approach is effective in improving the quality of learning and supporting the strengthening of the Pancasila Student Profile. This media is an innovative solution for interactive learning that is relevant to the educational needs of the 21st century. This research recommends the use of STEAM-based learning media to support learning in elementary schools, especially in grade 5 elementary school digestive system material, with further improvements to increase accessibility and efficiency. ABSTRAKPenelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis proyek dengan pendekatan STEAM (Science, Technology, Engineering, Arts, and Mathematics) guna mendukung penguatan Profil Pelajar Pancasila, khususnya pada dimensi mandiri dan bernalar kritis. Penelitian ini menggunakan model Research and Development (R&D) dengan pendekatan ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subjek penelitian adalah siswa kelas 5A SD Negeri Danasari 01 Kabupaten Tegal, Semester 1 Tahun Pelajaran 2024/2025. Proses pengembangan melibatkan validasi ahli, pengujian kepraktisan, dan evaluasi efektivitas. Media pembelajaran dirancang menggunakan Platform Canva dan Assembler Edu dengan konten interaktif yang mencakup video, gambar bergerak, dan soal latihan. Validasi oleh ahli menunjukkan hasil sangat valid dengan rata-rata skor validitas media 82% dan validitas materi 86%. Media dinilai sangat praktis dengan skor kepraktisan 95% oleh guru dan 80% oleh siswa. Implementasi media pembelajaran menunjukkan hasil signifikan dalam meningkatkan kemandirian (78%) dan kreativitas (76%) pada siswa. Analisis hasil pembelajaran menggunakan uji-t menunjukkan adanya perbedaan signifikan antara kelas eksperimen dan kelas kontrol, dengan nilai rata-rata post-test masing-masing 79,07 dan 66,22 (sig. 0,001 < 0,05). Evaluasi akhir mengungkap beberapa kendala teknis, seperti ukuran file yang besar dan aksesibilitas tautan, yang diatasi melalui pengoptimalan ukuran file dan penambahan elemen visual. Hasil penelitian ini menunjukkan bahwa media pembelajaran berbasis proyek dengan pendekatan STEAM efektif meningkatkan kualitas pembelajaran dan mendukung penguatan Profil Pelajar Pancasila. Media ini menjadi solusi inovatif dalam pembelajaran interaktif yang relevan dengan kebutuhan pendidikan abad ke-21. Penelitian ini merekomendasikan penggunaan media pembelajaran berbasis STEAM dalam mendukung pembelajaran di sekolah dasar, khususnya pada materi sistem pencernaan kelas 5 SD, dengan perbaikan lebih lanjut untuk meningkatkan aksesibilitas dan efisiensi.